Pengukuran Tingkat Financial Anxiety Dalam Kehidupan Gen Z Kota Samarinda - Aura Aziza; Ratna Fitri Astuti; Reza Reza; Sudarman Sudarman; Noor Ellyawati (Jayapangus Press, 2026)
Individuals are at risk of facing uncertainty that can lead to financial anxiety if they lack proper financial planning. Financial anxiety arises from suboptimal financial management, a lack of budgeting habits, and a tendency to prioritize non-essential consumption. This study aims to measure the level of financial anxiety among Gen Z in Samarinda City and identify the most dominant indicators influencing it. The study used a quantitative approach with a descriptive design. A sample of 100 respondents aged 19–24 years was determined using the Slovin formula with an accidental sampling technique. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics in the form of averages and percentages. The results showed that the majority of respondents (68%) were in the high financial anxiety category, while only a small proportion were in the low and very low categories. The main causes include not being accustomed to budgeting and not recording expenses. The most dominant indicator is the inability to adjust expenses, as reflected in unplanned expenses, the absence of financial evaluations, and the absence of an emergency fund. Gen Z in Samarinda City still faces challenges in financial management that impact high financial anxiety, so it is necessary to improve literacy and discipline in financial planning.